Upaya Meningkatkan Hasil Belajar Siswa Sekolah Dasar Materi Menyambut Usia Baligh - Darkasih Darkasih; Azizah Aryati (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study was motivated by issues in Islamic Religious Education (PAI) lessons at SDN 045/V Teluk Nilau, particularly about